Evaluation of Silver Nanoparticles (Ag NPs) Activity Against the Viability of Leishmania tropica Promastigotes and Amastigotes In Vitro - Gharby , Meaad, A.; AL-Qadhi, Ban N.; Jaafar, Sadeq M. (Iraqi Journal of Science, 2022)
Leishmaniasis is a disease caused by a protozoan parasite of the genus Leishmania. It is transmitted by the bite of sandfly (Subfamily Phlebotominae). Limited drugs are available for the treatment of leishmaniasis, and the general drug (pentostam) have many side effect on patients. Therefore, there is an urgent need for another drugs for the treatment of leishmaniasis.This study aimed to develop new type of antileishmanial agents instead of classical drug (pentostam) and investigated the effectiveness of silver nanoparticles (Ag NPs) on Leishmania tropica parasites in both phases promastigote and amastigote in comparision to pentostam in in vitro condition.This study showed the effects of Ag NPs in comparision to pentostam with different concentrations (0.3, 0.6, 0.9, 1.2, 1.5, 1.8 and 2.1 μg/ ml) on L.tropica promastigotes viability. The viability of promastigotes after 72 hr. recorded maximum cytotoxic effect of Ag NPs in highest concentration (2.1 μg/ml), it was 23.17 ± 0.45 % comparing with pentostam which was 69.33 ± 0.33 %, as well as IC50 was calculated for MTT assay and the result for Ag NPs was 1. 749 μg/ml after 72 hr., while pentostam drug did not show IC50 in all treatments.On the other hand, the study also showed the effects of Ag NPs on L.tropica amastigote phase, and the viability was (3.10 ± 0.59 and 47.34 ± 0.87) % after 72 hr. in the highest concentration 2.1 μg/ml for Ag NPs and pentostam respectively, and IC50 was 1.148 μg/ ml for Ag NPs after 72 hr., but all results of pentostam stayed over than 50%.